Meniscus Injury and its Surgical Treatment Does not Increase Initial Whole Knee Joint Friction - de Roy, Luisa; Warnecke, Daniela; Hacker, Steffen Paul; Simon, Ulrich; Dürselen, Lutz; Ignatius, Anita; Seitz, Andreas Martin (Frontiers in Bioengineering and Biotechnology, 2021)
While it is generally accepted that traumatic meniscus pathologies lead to degenerative articular cartilage changes in the mid- to long-term and consecutively to post-traumatic osteoarthritis (PTOA), very little is known about how such injuries initiate tribological changes within the knee and their possible impact on PTOA acceleration. Therefore, the aim of this study was to investigate the influence of three different medial meniscus states (intact, posterior root tear, total meniscectomy) on the initial whole knee joint friction. Six ovine knee joints were tested in a passive pendulum friction testing device under an axial load of 250 N and an initial deflection of 12°, representing swing phase conditions, and under an axial load of 1000 N and an initial deflection of 5°, simulating stance phase conditions. To additionally consider the influence of the time-dependent viscoelastic nature of the knee joint soft tissues on whole joint friction, the tests were performed twice, directly following load application and after 20 minutes creep loading of either 250 N or 1000 N axial load. On the basis of a three-dimensional joint kinematic analysis, the initial whole knee joint friction was evaluated using the boundary friction model from Stanton and a viscous friction model from Crisco et al., both analyzing the passive joint flexion-extension motion in the sagittal plane. Significantly lower friction coefficients were observed in the simulated swing phase after meniscectomy (p<0.05) compared to the intact state. No initial whole joint friction differences between the three meniscus states (p>0.05) were found under stance phase conditions. Soft tissue creeping significantly increased all the determined friction coefficients (p<0.05) after resting under load for 20 minutes. The exponential decay function of the viscous friction model provided a better fit (R²~0.99) to the decaying flexion-extension data than the linear decay function of the boundary friction model (R²~0.60). In conclusion, this tribological in vitro study on ovine knee joints indicated that neither a simulated posterior medial meniscus root tear nor the removal of the medial meniscus resulted in an initially increased whole joint friction.